HUBUNGAN KEKUATAN OTOT LENGAN DENGAN PRESTASI LEMPARAN BOLA KE DALAM PADA PERMAINAN SEPAK BOLA PADA SISWA PUTRA KELAS VI SDN 1 JENGGIK LOTIM TAHUN PELAJARAN 2014/2015. - jama'urrahban jama'urrahban (Universitas Pendidikan Mandalika, 2016)
One of the most popular games at the elementary level has even spread to the remote corners of the village is a game of football, this can not be denied again. Football game not only conducted between classes or clubs, but often also held between the schools, the group even at the provincial level. Therefore needed skills in performing basic techniques which owned the game of football. One of them is the toss. The problems in this study is whether there Relations Arm Muscle Strength Achievement Throw Ball Into the Student Games Men's Football in Class VI SDN 1 Jenggik Lotim Academic Year 2014/2015? While the purpose of the research was to find out relationship Arm Muscle Strength Achievement Throw Ball Into the Student Games Men's Football in Class VI SDN 1 Jenggik Lotim in the academic year 2014/2015. The population in this study were all male students at SDN 1Jenggik sixth grade in the school year 2014/2015, amounting to 15 students, while the researchers used a sample of 100% so that the sampling technique used in this research is the study population. To obtain the data needed to support the success of the research, it is necessary a method for data collection. In accordance with the objectives of this study, the method used is the test method works to obtain data on the arm muscle strength using the push-ups for one minute and throw the ball in a football game and methods of documentation as a backup method. From the analysis of the data obtained rxy obtained at 0.718 and r table at significant level of 5% with N = 15 is 0.514, it means that the value of r count is greater than r table (0.718> 0.514). so it concluded that